PENGARUH KOMBINASI PUPUK ANORGANIK DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) DI LAHAN PASIR - Rahma Estu Wulan Sari; Yekti Maryani; Darnawi (JURNAL ILMIAH AGROUST, 2026)
The research aimed to examine and determine the effect between the use of inorganic fertilizers and chicken manure on the growth and yield of shallot plants in sandy soil. The research was conducted from May to July 2024. It took place on the sandy land of the Ngudi Mulyo farmer group in Parangtritis, Kretek, Bantul, Yogyakarta Special Region. The research site is located along the coast, at an elevation of 2 meters above sea level and approximately 400 meters from the coastline. The average annual temperature is 30℃, with a humidity level of 70– 80%, and the average monthly rainfall is 31 mm. The study was arranged using a Randomized Complete Block Design (RCBD) with two factors. The first factor was organic fertilizer, consisting of No Manure (A0) and Chicken Manure (A1). The second factor was inorganic fertilizer, consisting of No Inorganic Fertilizer (K0), NPK (K1), NP (K2), NK (K3), and KP (K4). The observed variables included growth variables plant height, number of leaves, number of plants, fresh biomass weight, and dry biomass weight and yield variables bulb diameter, average biomass weight, average clean bulb weight, and clean bulb weight per hectare. Observation results were analyzed using analysis of variance (ANOVA) at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) at a 5% level. The results showed that there was no interaction between the application of organic and inorganic fertilizers on the growth and yield variables. Organic fertilizer treatment showed a significant difference in plant height, number of plants, and fresh biomass weight, with the highest results observed in the chicken manure treatment. However, organic fertilizer treatment showed no significant difference in the yield of shallots. Inorganic fertilizer treatment showed no significant difference in both the growth and yield of shallots.